Inactivation of folylpolyglutamate synthetase Met7 results in genome instability driven by an increased dUTP/dTTP ratio - Schmidt, Tobias Thomas; Hombauer, Hans; Kolodziejczak, Anna (Nucleic acids research, 2020)
Abstract. The accumulation of mutations is frequently associated with alterations in gene function leading to the onset of diseases, including cancer. Aiming t